Cell-free layer measurements in bifurcating microchannels: a global approach - Taboada, Bruna Rafaela Pereira (2014)
In the present work, in vitro blood flowing through bifurcating microchannels was studied, with the aim of characterizing the cell-free layer (CFL). The original images were obtained by means of a high-speed video microscopy system and then processed in MatLab using the Image Processing Toolbox. The numerical data was obtained automatically and analyzed by optimization techniques using the genetic algorithm approach. The results suggest that the CFL were formed in a similar way at the upper and lower regions in all bifurcations, and the measurements can be approximated through a sum of trigonometric functions.